Experimental morphological study of reparative processes in oral mucosa erosive lesions - Poroisky, Sergey V.; Macedonova, Julia A.; Firsova, Irina V.; Poroiskaya, Anna V.; Trigolos, Natalia N. (Journal of Stomatology, 2017)
The urgency of the problem under consideration is due to a relatively high prevalence of erosive lesions in the oral mucosa characterized by prolonged disease progression. Given a considerable arsenal of various medications and their combinations, a medical specialist today finds him/herself in an ever-difficult situation of having to make the right choice of medicine in order to quickly and efficiently stop an oral lesion, speed up the healing process and facilitate recovery of the reparative function in the affected tissue. The goal of the study is to substantiate the effectiveness of using platelet auto plasma to heal erosive lesions in the oral cavity. The leading method of this study is morphological analysis of qualitative and semiquantitative parameters, allowing us to reveal and specify the state of oral mucosa. The study results demonstrated that, in morphological terms, the best aspect of disease was observed in the group of patients receiving autohaemotherapy, where no traces of lesion symptoms were found. In the reference group, during this observation period, there were signs of nonspecific non-chronic inflammation in certain zones of oral mucosa. Materials of this paper may be useful in dental practice for healing various inflammatory disorders in the facial maxillary area.